Temporal and amplitude modulation at C-band region using Bi2Te3-based optical modulator - Ahmad, Harith; Yusoff, Norazriena; Lim, Hwee San; Mat Jafri, Mohd Zubir; Zulkifli, Mohd Zamani; Tiu, Zian Cheak (Taylor and Francis Ltd., 2020)
A temporal and amplitude modulator based on few-layers bismuth telluride (Bi2Te3) flakes is demonstrated for C-band operation. The few-layers thick Bi2Te3 flakes are prepared by mechanically exfoliating a Bi2Te3 crystal. As an optical pulse modulator, the Bi2Te3-based saturable absorber (SA) provides stable Q-switching operation at 1561.1 nm with a maximum repetition rate of 70.92 kHz and minimum pulse width of 2.38 µs. As an optical amplitude modulator, two linear regions at different pump power ranges are obtained in the regression line of the peak intensity. The first linear region covers a pump power range from 0.0 to 80.32 mW and corresponds to a modulation efficiency of 0.05 dB/mW, while the second linear region covers a pump power range of 80.32–98.64 mW with a modulation efficiency of 0.81 dB/mW.